Oral history as a tool for exploring mental structures of peace and migration in the context of the contemporary russo-ukrainian war. - Bilivnenko , Serhii; Petrova , Kateryna (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2025)
Research aim is to explore how oral history interviews reflect the transformations of mental structures within Ukrainian society during the contemporary Russo-Ukrainian war, particularly through the analysis of categories such as “security/insecurity,” “refugees/internally displaced persons,” language choice, and respondents’ adaptation during migration.Methodology of the research is based on the analysis of oral history materials (interviews with forced migrants from 2022–2024), employing qualitative methods (comparative narrative analysis, identification of mental patterns), as well as an interdisciplinary approach that combines tools from history, sociology, psychology, and cultural anthropology.The scientific novelty of the study lies in identifying mental patterns among forced migrants during the Russo-Ukrainian war of 2022–2024 based on oral history materials, and in demonstrating the dependence of narrative expression readiness on the respondents’ attainment of a “security mode.” It is proposed to consider oral history not only as a method of source collection but also as a tool of social policy and a means of documenting transformations of social identity under wartime conditions.Conclusions. Based on the analysis of oral history interviews, the effectiveness of oral history as a tool for studying migration processes caused by the full-scale invasion is substantiated, as it allows for the recording not only of displacement facts but also of mental patterns, emotional reactions, and identity transformations. It is confirmed that a significant factor in respondents’ willingness to share their experiences is the attainment of a “security mode”—a state in which a person feels protected and capable of reflection. The potential of oral history as a tool of social policy is revealed, particularly through providing respondents with a sense of significance and inclusion in the historical process during interviews. Prospects for further oral history research are outlined, in which repeated interviews, interdisciplinary approaches to analyzing oral testimonies, and the combination of narratives with visual and personal sources (diaries, photographs, drawings, digital memes) may play a key role.